“Men Cannot Be Raped”: Correlates of Male Rape Myth Acceptance - Walfield, Scott M. (Journal of interpersonal violence, 2021)
Despite the increased attention surrounding rape and sexual assault, research on male victims remains limited, particularly concerning the adherence to rape myths. Rape myths, which are false beliefs that are widely accepted, contribute to the justification and normalization of sexual violence by offenders and focus on the actions and behavior of victims while minimizing the harm. Addressing the gaps in the research, the present study examines how demographics, personal experiences with rape (i.e., being or knowing a survivor), and belief systems relate to rape myth adherence for male victims. The sample consisted of 1,220 adults in the United States who completed an online survey via Amazon’s Mechanical Turk (MTurk). The number of myths endorsed ranged from 0 to 21 with a mean of 4.1 (SD = 4.7). In the final model of the hierarchical regression, results indicate rape myth acceptance was positively associated with individuals who were male, older, and more likely to believe males falsely report rapes to law enforcement at a high rate. Of the gender and sexuality attitudinal scales, individuals who adhered to female rape myths, held negative attitudes toward homosexuals, accepted traditional sexual double standards, and believed in traditional social gender roles were more likely to adhere to male rape myths. Findings demonstrate that rape myths operate similarly for male and female victims. Sexual assault programming and interventions need to address that males can be victims of sexual violence and the myths associated with male victimization in addition to generally challenging the adverse belief systems that serve as the foundation for rape myths generally.